A Comparative Study on The Effect of Cooking Methods on The Nutritional Contents of Ripe and Unripe Plantain (Musa Paradisiaca) - Stanley Udogadi Nwawuba; Nwozo Sarah Onyenibe (Indonesian Association of Food Technologists, 2021)
Plantains are conventionally consumed either after boiling, steaming, roasting or frying which are there major cooking methods employed in the utilization in Nigeria. Method of preparation and cooking could either reduce or improve the nutrient quality of foods. Thus the objective of the present study was to investigate the effect of cooking methods on the nutritional content of ripe and unripe plantain. Ripe and unripe plantain was obtained and divided into four (4) portions; raw which served as the control, boiled, fried and roasted. Analysis of the proximate, vitamin and mineral content of the samples were carried out using standard methods and our result revealed that boiling as a cooking method significantly retained the levels of minerals, vitamins and proximate composition of ripe and unripe plantain relative to frying and roasting. In conclusion we recommend that boiling should be predominately employed during cooking of neither ripe nor unripe plantain.